Pharmaceutical Grade Microcrystalline Cellulose from Corn Husk (Zea mays L.): Fabrication and Characterization - Cahyani, Intan Martha; Ikasari, Endang Diyah; Tadlkirotulladlat, Novi; Anggraini, Novita Sindy (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Corn is a plant that grows easily in tropical climates. Corn production in Indonesia reaches 25.18 tons, the use of which in society is still limited to corn kernels as food, while other parts of the corn plant are waste. Corn husks are an abundant natural waste and contain 44.08% cellulose, so they can potentially be a source of pharmaceutical excipients, namely microcrystalline cellulose (MCC). This research aims to isolate and characterize MCC from pharmaceutical grade corn husks with commercial MCC as a comparator. The two methods of making MCC are delignification using 2% NaOH at 80-90°C 4 h. Hydrolysis using variations in HCl concentrations, namely 2 N, 4 N, and 6 N, at a temperature of 80°C 4 h. The research results obtained cellulose content in α-cellulose and MCC of corn husks with 3 consecutive treatments of 74.02%, 84.48%, 86.55%, and 84.44%. The result of the analysis test of FTIR, SEM, XRD, and PSA instruments indicate that corn husk MCC has characteristics of commercial MCC as a standard. The resulting corn husk MCC has physicochemical characteristics according to standards that can be used as a pharmaceutical excipient.